2011
DOI: 10.1177/0892705711411344
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, mechanical, and thermal characterization of high-density polyethylene composites with ground tire rubber

Abstract: The mass manufacture of tires and the difficulty in storing or disposing them constitute\ud a serious environmental problem. At present, various recycling methods for tires are\ud used, such as grinding, which separates the steel and fibers from the vulcanized rubber,\ud then using the rubber in numerous industrial applications such as pavements, insulators,\ud footwear, etc. The aim of this article focuses on finding a new application for the ground\ud tire rubber (GTR). This would allow including GTR in indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…In present, composite materials with a recycled PVC matrix mixed with plasticized PVC and an armature with grinding rubber from waste have been made, and the results obtained showed that such a composite material has interesting acoustic properties at frequencies higher than 2500 Hz. Additionally, the use of ground rubber waste has led to an improvement in the rigidity of such composite materials with an increase in Young’s modulus, but also to a slow decrease in tensile strength, elongation at break and hardness [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In present, composite materials with a recycled PVC matrix mixed with plasticized PVC and an armature with grinding rubber from waste have been made, and the results obtained showed that such a composite material has interesting acoustic properties at frequencies higher than 2500 Hz. Additionally, the use of ground rubber waste has led to an improvement in the rigidity of such composite materials with an increase in Young’s modulus, but also to a slow decrease in tensile strength, elongation at break and hardness [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global problem of the accumulation of used tires as stores [1,2] has driven the efforts of the scientific community to search for solutions for recovery and reuse of this wasted material. The use of this ground tire rubber (GTR) as reinforcements in composite materials has been widely studied in several works [3]. The presence of GTR in polymer matrix composite materials modifies both the dielectric and mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A large of that iron originates from recycling scraps, such as old cars, cans, bridges, rails and demolished buildings. There are some reports on preparing high dielectric constant (high-k) composites with industry wastes, such as ground tire rubber [4] and red mud [5,6]. As in this process, some metals such as zinc protecting on the surface of steel are also oxidized into dust.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has seldom been studied [1][2][3]. There are some reports on preparing high dielectric constant (high-k) composites with industry wastes, such as ground tire rubber [4] and red mud [5,6]. Considering the composition of CA, it can be used to prepare high-k polymer composites.…”
Section: Introductionmentioning
confidence: 99%